2004
DOI: 10.1111/j.1365-2710.2004.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of atypical antipsychotic agents and health outcomes in patients with schizophrenia

Abstract: Despite olanzapine and risperidone being often perceived as similar antipsychotic agents, our results suggest that the clinical outcomes associated with their use are different. Outcome data from routine clinical practice are required to provide a more comprehensive assessment of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In the United States, olanzapine initiators were found to have more complex psychiatric histories than risperidone initiators including more pre-existing psychiatric comorbidities [20], more prior use of other classes of psychiatric medications [20,21], higher prior psychiatric inpatient costs [22], more previous treatment with clozapine [21,23,24], and more initial prescriptions from psychiatrists [24]. Consistent with these prior studies, olanzapine initiators in the current analysis were more likely to have diagnoses for manic episodes and had more prior antidepressant use.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the United States, olanzapine initiators were found to have more complex psychiatric histories than risperidone initiators including more pre-existing psychiatric comorbidities [20], more prior use of other classes of psychiatric medications [20,21], higher prior psychiatric inpatient costs [22], more previous treatment with clozapine [21,23,24], and more initial prescriptions from psychiatrists [24]. Consistent with these prior studies, olanzapine initiators in the current analysis were more likely to have diagnoses for manic episodes and had more prior antidepressant use.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with these prior studies, olanzapine initiators in the current analysis were more likely to have diagnoses for manic episodes and had more prior antidepressant use. In the United States, risperidone was found to be initiated more often than olanzapine for patients with schizophrenia who have more physical comorbidities [20,[22][23][24][25]. Consistent with these studies, the univariate analysis found that risperidone initiators were more likely to have previous claims for diabetes mellitus.…”
Section: Discussionmentioning
confidence: 53%
“…Since poor treatment persistence contributed to an estimated 40% relapses (Weiden and Zygmund 1997), levels of treatment persistence have become an increasingly important factor in prescription choices by physicians of different antipsychotic agents. However, considering the inappropriateness of the conventional approach in measuring treatment persistence as well as the limitations of the present study, more research is needed to examine the extent to which adjunctive use of other agents, a common practice among patients with schizophrenia (Ren et al 2004), will influence levels of treatment persistence. Future research should also assess the impact of poor treatment persistence on a wide spectrum of patient outcomes (Ren et al 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…In other medication studies involving patients diagnosed with schizophrenia and their anti-psychotic use, Ren et al [2002bRen et al [ , 2004Ren et al [ , 2005b merged patientreported HRQoL data (VR-36) and utilization of psychiatric services with medication history that includes dosage and duration of use on the basis of 89,107 subjects. Using a cohort design, results show that olzanzapine and risperidone users were associated with different sociodemographic characteristics; those on olanzapine compared to those on risperidone were younger (Po0.001), Hispanic (Po0.001), with fewer medical co-morbidities and a lower body mass index (Po0.05).…”
Section: Utilization Of Services and Medication Therapymentioning
confidence: 99%